2013
DOI: 10.1124/jpet.113.208496
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Distinction between Soluble and Transmembrane Adenylyl Cyclases

Abstract: The second messenger cAMP is involved in a number of cellular signaling pathways. In mammals, cAMP is produced by either the hormonally responsive, G protein-regulated transmembrane adenylyl cyclases (tmACs) or by the bicarbonate-and calcium-regulated soluble adenylyl cyclase (sAC). To develop tools to differentiate tmAC and sAC signaling, we determined the specificity and potency of commercially available adenylyl cyclase inhibitors. In cellular systems, two inhibitors, KH7 and catechol estrogens, proved spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(131 citation statements)
references
References 71 publications
6
122
0
3
Order By: Relevance
“…The same authors observed regulation by GTP analogs as well as with mastoparan, a wasp venom toxin known to activate G proteins. In addition, in this study, the effect of FK was blocked by SQ22536, a compound known to inactivate tmACs in several cell types with an IC 50 value that varies depending on the tmAC isoform but not by the specific AdCy10 inhibitor KH7 (44).…”
Section: Journal Of Biological Chemistry 35315mentioning
confidence: 66%
“…The same authors observed regulation by GTP analogs as well as with mastoparan, a wasp venom toxin known to activate G proteins. In addition, in this study, the effect of FK was blocked by SQ22536, a compound known to inactivate tmACs in several cell types with an IC 50 value that varies depending on the tmAC isoform but not by the specific AdCy10 inhibitor KH7 (44).…”
Section: Journal Of Biological Chemistry 35315mentioning
confidence: 66%
“…3D and 4A, GST-tagged sAC-cat lysate was used in a radioactivitybased assay in 50 mM Tris (pH 7.5) under the conditions indicated in a reaction containing ∼1,000,000 counts of α-32 P-labeled ATP as described previously (47). Generated cAMP was purified using sequential Dowex and Alumina chromatography as described previously (48).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, there is reasonably good agreement in the obtained pIC 50 values (Table 7). SQ22,536, NKY80, and vidarabine exhibit some degree of selectivity among AC isoforms, AC2 being relatively insensitive compared with ACs 5 and 6 (Bitterman et al, 2013). ACs 8 and 9 and sAC are very resistant to inhibition by SQ22,536, NKY80, and vidarabine.…”
Section: +mentioning
confidence: 99%
“…Data for mACs 1, 2, and 5 and 5C1:2C2 were taken from the literature as noted by the footnotes. Bitterman et al, 2013;Braeunig et al, 2013;Braeunig et al, 2014). Table 7 lists the pIC 50 values of these compounds for inhibition of ACs and pK i values for interaction with adenosine receptors.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation